Revisiting William Shakespeare: Exploring human nature and the complexities of the human mind in William Shakespeare's works (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It has been contended that general human behaviorist propelled by the nature the nature and characteristics of the human brain. Utilizing a blend of unfortunate and comic tones, Shakespeare considered human nature and gave a significant and profound examination of the human brain in Hamlet and Macbeth. With this impact, the writer looks at the battle of the human soul out of dimness of mistakes and sin, so as to find truth and insight. He utilizes Hamlet as a hero whose interest mirrors the human mission for truth about the reasons that make the world undermined. He likewise utilizes Macbeth to show that dull idea and oblivious allurements cause a man who needs quality of character to do horrible activities. Through discourses in Hamlet and Macbeth and an intelligent examination of their human characteristics, Shakespeare distinguishes the multifaceted nature of the human brain. These two plays reflect practical and general perspectives on psychological and psychoanalytical human highlights in life undertakings and their cooperation with their destinies.